Update: Global Reaction To Kosovo Crisis. - United States Information Agency. Office of Research and Media Reaction.; Bell, Janice, 1968-; Smeltz, Dina.; Grant, Steve. (Tufts University. Tisch Library., 2019)
NATO's bombing of a Kosovo Albanian refugee convoy has had a varied impact on public opinion toward Kosovo. Support for NATO or its actions has remained stable in Germany and France, but has dropped off in Britain, Italy and front-line countries. Still, many publics appear to be ahead of governments in their anticipation of the need to introduce ground forces.; [European Opinion Alert?] L-22-99